Cytotoxicity and Immunomodulatory Effects of Cannabidiol on Canine PBMCs: A Study in LPS-Stimulated and Epileptic Dogs - Phannicha Kosukwatthana; Oumaporn Rungsuriyawiboon; Jatuporn Rattanasrisomporn; Kanogwan Kimram; Natthasit Tansakul (Animals)
Cannabidiol, the primary non-psychoactive phytocannabinoid found in cannabis, has generated significant research interest due to its potential for biological effects, such as anti-inflammatory, analgesic, immunomodulatory, and anticonvulsant properties. Several studies have demonstrated the potential of CBD to alter inflammatory cytokines; however, data on CBD’s effects on cell viability and pro-inflammatory cytokines in target animals, such as dogs, are limited. Therefore, in this study, we investigated the effects of CBD on the cell viability and modulation of pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α), in canine PBMCs stimulated with LPS. To evaluate the effect of CBD on neuroinflammation in epilepsy pathology, an independent study of five refractory epileptic dogs co-treated with CBD for 30 days was conducted. The current findings revealed that CBD concentrations of 16 µg/mL had a statistically significant effect on the viability of canine PBMCs with a calculated IC50 of 15.54 µg/mL. The effect of CBD on inflammatory cytokines in LPS-stimulated PBMCs tended to be dose-dependent, with CBD concentrations of 5–30 μg/mL resulting in decreased production of the tested pro-inflammatory cytokines. Considering the effect of CBD on cytokine production by PBMCs from epileptic dogs, CBD has the potential to modulate immune responses and provide benefits when used in combination with antiepileptic drugs. The findings provided evidence of CBD cytotoxicity and its effect on the alteration of pro-inflammatory cytokines in canine PBMCs.